Inhibiting Histone Deacetylases in Human Macrophages Promotes Glycolysis, IL-1β, and T Helper Cell Responses to Mycobacterium tuberculosis - Cox, Donal J.; Coleman, Amy M.; Gogan, Karl M.; Phelan, James J.; Ó Maoldomhnaigh, Cilian; Dunne, Pádraic J.; Basdeo, Sharee A.; Keane, Joseph (Frontiers in Immunology, 2020)
Tuberculosis (TB) is the leading infectious killer in the world. Mycobacterium tuberculosis (Mtb), the bacteria that causes the disease, is phagocytosed by alveolar macrophages (AM) and infiltrating monocyte-derived macrophages (MDM) in the lung. Infected macrophages then upregulate effector functions through epigenetic modifications to make DNA accessible for transcription. The metabolic switch to glycolysis and the production of proinflammatory cytokines are key effector functions, governed by epigenetic changes, that are integral to the ability of the macrophage to mount an effective immune response against Mtb. We hypothesised that suberanilohydroxamic acid (SAHA), an FDA-approved histone deacetylase inhibitor (HDACi), can modulate epigenetic changes upstream of the metabolic switch and support immune responses during Mtb infection. The rate of glycolysis in human MDM, infected with Mtb and treated with SAHA, was tracked in real time on the Seahorse XFe24 Analyzer. SAHA promoted glycolysis early in the response to Mtb. This was associated with significantly increased production of IL-1β and significantly reduced IL-10 in human MDM and AM. Since innate immune function directs downstream adaptive immune responses, we used SAHA-treated Mtb-infected AM or MDM in a co-culture system to stimulate T cells. Mtb-infected macrophages that had previously been treated with SAHA promoted IFN-γ, GM-CSF and TNF co-production in responding T helper cells but did not affect cytotoxic T cells. These results indicate that SAHA promoted the early switch to glycolysis, increased IL-1β and reduced IL-10 production in human macrophages infected with Mtb. Moreover, the elevated proinflammatory function of SAHA-treated macrophages resulted in enhanced T helper cell cytokine polyfunctionality. These data provide an in vitro proof-of-concept for the use of HDACi to modulate human immunometabolic processes in macrophages to promote innate and subsequent adaptive proinflammatory responses.